2021
DOI: 10.1111/jocd.13961
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microfocused ultrasound with visualization for skin laxity among vegan and omnivore patients

Abstract: Background The aging of facial structures depends on genetic, anatomic, chronologic, and environmental factors that affect the skin and underlying tissues. Microfocused ultrasound with visualization (MFU‐V) has emerged as a safe and effective treatment for skin laxity. As the nutritional status may contribute to skin aging, it would be interesting to evaluate whether different dietary patterns can also influence the response to MFU‐V treatment for skin laxity. Aims The aim of this study is to compare the outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…19 Furthermore, it was reported that the clinical response of vegan participants to microfocused ultrasound treatment to reduce skin laxity was lower and there was a new worsening in skin laxity rates at Month 6 compared to pretreatment levels. 20 In the present study, there was an increase in skin rejuvenation and quality in both groups, observed by a decrease in the posttreatment FWS scores. The aforementioned increase in skin quality was significantly lower in the vegan participants.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…19 Furthermore, it was reported that the clinical response of vegan participants to microfocused ultrasound treatment to reduce skin laxity was lower and there was a new worsening in skin laxity rates at Month 6 compared to pretreatment levels. 20 In the present study, there was an increase in skin rejuvenation and quality in both groups, observed by a decrease in the posttreatment FWS scores. The aforementioned increase in skin quality was significantly lower in the vegan participants.…”
Section: Discussionsupporting
confidence: 57%
“…A recent publication reported that vegan participants had more side effects and a prolonged periods for wound healing and skin regeneration due to the prolonged inflammatory response and healing time following photodynamic treatments for actinic keratosis 19 . Furthermore, it was reported that the clinical response of vegan participants to microfocused ultrasound treatment to reduce skin laxity was lower and there was a new worsening in skin laxity rates at Month 6 compared to pretreatment levels 20 . In the present study, there was an increase in skin rejuvenation and quality in both groups, observed by a decrease in the posttreatment FWS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Fusano et al reported on 54 vegan and omnivore patients with MFU‐V at 4.0 MHz‐4.5 mm and 7.0 MHz‐3.0 mm depth parameters, using three points scale scoring 74% of the omnivorous patients were very satisfied, and 26% were satisfied 6 months post‐treatment 6 …”
Section: Resultsmentioning
confidence: 99%
“…Fusano et al reported on 54 vegan and omnivore patients with MFU-V at 4.0 MHz-4.5 mm and 7.0 MHz-3.0 mm depth parameters, using three points scale scoring 74% of the omnivorous patients were very satisfied, and 26% were satisfied 6 months post-treatment. 6 In 2020, Yalici-Armagan and Elcin treated 24 patients with lower facial and submental laxity, using the original parameter of 7.5 MHz with a focal depth of 3.0 mm and 4 MHz with a focal depth of 4.5 mm.…”
Section: Re Sultsmentioning
confidence: 99%